Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.1080/21553769.2015.1051244
|View full text |Cite
|
Sign up to set email alerts
|

Selective isolation and antagonistic activity of actinomycetes from mangrove forest of Pahang, Malaysia

Abstract: This study aimed to isolate and evaluate the antagonistic potential of actinomycetes from mangrove forest of Pahang, Malaysia. Sediment samples from seven different sites were pretreated using wet heat and dry heat methods followed by dilution plating on eight isolation media. In total, 4850 isolates were successfully recovered, with inorganic salt-starch agar displaying the highest percentage of recovery (31.7%), followed by actinomycete isolation agar (24.1%). The wet heat pretreatment was found to be more e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 28 publications
0
15
0
1
Order By: Relevance
“…Reduced concentration of polymerases ensure specificity while higher counterpart causing nonspecific amplicons [19]. DNA polymerases are favored in PCR process with a cofactor like magnesium ion [20]. They are easily manipulated resulting in the stringency of PCR as its ionic concentration is critical.…”
Section: Resultsmentioning
confidence: 99%
“…Reduced concentration of polymerases ensure specificity while higher counterpart causing nonspecific amplicons [19]. DNA polymerases are favored in PCR process with a cofactor like magnesium ion [20]. They are easily manipulated resulting in the stringency of PCR as its ionic concentration is critical.…”
Section: Resultsmentioning
confidence: 99%
“…This is could be due to the fact that the location of downstream and midstream point of Balok River is near to residential areas whereby the housing discharge from residential areas might be dumped to Balok River from the nearby housing drains. In particular, downstream point of Balok River is also near to mangrove forest area that might increase the probability of getting Cryptosporidium oocysts on surface river water even this area is also adjacent to estuary of Balok River heading to South China Sea [19]. In fact, the upstream point of Balok River is also located near to forest area where zoonotic transmission of Cryptosporidium oocysts can possibly happen and infect nearby river water stream [19].…”
Section: Discussionmentioning
confidence: 99%
“…In particular, downstream point of Balok River is also near to mangrove forest area that might increase the probability of getting Cryptosporidium oocysts on surface river water even this area is also adjacent to estuary of Balok River heading to South China Sea [19]. In fact, the upstream point of Balok River is also located near to forest area where zoonotic transmission of Cryptosporidium oocysts can possibly happen and infect nearby river water stream [19]. In contrast, only one water sample from the upstream point of Kuantan River was detected to be negative for C. parvum.…”
Section: Discussionmentioning
confidence: 99%
“…1). However, several previous studies reported lower percentages of antagonistic isolates among actinomycetes isolated from marine environments [17][18][19] . Only 2 isolates (12.5%) did not exhibit any antimicrobial activity against any of the pathogens tested.…”
Section: Isolation and Screening Of Marine Actinomycetesmentioning
confidence: 99%